IMPLEMENTATION OF THE POGIL LEARNING MODEL INTEGRATED MIND MAP BASED ON ONLINE LEARNING TO IMPROVE COMMUNICATION AND COLLABORATION SKILLS OF AL MAARIF SINGOSARI ISLAMIC SMA STUDENTS - Binazir T Tuza Qiyah Ma’rufah; Herawati Susilo; - Balqis; Ahmad Kamal Sudrajat (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
Abstract—Communication and collaboration skills must be possessed in the 2013 curriculum learning to face the fierce job competition in the 21st Century. The results of observations and interviews of biology teachers at SMAI Al Maarif, students' communication and collaboration skills are still relatively low. This study aims to improve the communication and collaboration skills of Al Maarif Singosari Islamic High School students through the implementation of the POGIL learning model combined with online learning-based mind maps. This type of research is classroom action research. According to Kemmis and McTaggart, the CAR procedure consists of 4 stages, namely planning, implementing actions, observing, and reflecting, followed by the next spiral cycle. The research subjects were 35 students of class XI MIPA 3, totaling 35 people. The data in this study were oral communication and collaboration skills measured using observation sheets and written communication skills using students' worksheets. The results showed that implementing the POGIL learning model combined with online learning-based mindmaps could improve students' communication and collaboration skills. The highest increase in communication skills occurred in oral communication, which was 20,3%. Meanwhile, collaboration skills experienced the highest increase in the compromise indicator, which was 29.03%.Keywords—Collaboration; Communication; Mind map; Online Learning; POGIL